Alman Hukuku'nun İlamın Geçici İcrasına İlişkin Düzenlemelerine (vorläufige Vollstreckbarkeit) Genel Bir Bakış ve Türk Hukuku ile Karşılaştırılması - (:unkn) unknown (My University, 2017)
Çalışmamızda bizzat ihkakı hak yasağından dolayı devletin, alacaklıya icra hakkını tanıması gerektiği belirtildikten sonra, kısaca cüzi ile külli takip terimlerinin tanımı yapılacak ve her ikisi arasındaki temel farklar ele alınacaktır. Ayrıca ana hatları ile ilamsız icraya değinilecek ve gerek Türk Hukuku'nda ve gerekse Alman Hukuku'ndaki çözümler kısaca incelenecektir. Akabinde ilamlı icra ele alınacaktır. İlamların icrasının kural olarak kesinleşmeden mümkün olduğu gerek Türk Hukuku'nda gerekse Alman Hukuku'nda kabul edilmektedir. Bu bağlamda çalışmamızda her iki hukuk sisteminin benzerliklerini ve farklarını inceleyeceğiz ve özellikle Alman Hukuku'nda henüz kesinleşmemiş ilamların geçici icrasını irdeleyeceğiz. Alman Hukuku'ndaki söz konusu kurumun istisnaları da incelendikten sonra, Türk Hukuku'ndaki düzenlemeler ile kıyas edilecektir. Türk Hukuku ile Alman Hukuku'nun kesinleşmemiş ilamların icrası bakımından düzenlemeleri kıyas edildiğinde, Türk Hukuku'ndaki düzenlemelerin uygulamaya daha uygun olduğu anlaşılacaktır. Alman Hukuku'ndaki geçici icranın, Türk Hukuku'na nazaran farklı ve şaşırtıcı bir düzenleme olduğu da açıklanacaktır. Özellikle alacaklı ve borçlu arasındaki menfaat dengesinin korunması bakımından Türk Hukuku'ndaki İİK 36. maddenin başarılı bir madde olduğu sonucuna varılacaktır.

In this study we are going to define the enforcement and bankruptcy proceedings and to discuss the differences between those, after laying stress on the necessity of granting the right of enforcement to the creditor due to prohibition of enforcing of rights without resorting to judicial procedure. Besides we are going to touch upon the enforcement proceedings without judgement with the main lines and to examine the solutions both in German and Turkish law briefly. Subsequently we are going to talk over the enforcement proceedings with judgement. In principle it is accepted both in German and Turkish law that court decisions can be enforced before it becomes final. In this regard we are going to examine the similarities and the differences of these judicial systems and to analyse more specifically the provisional enforcement of German court decisions which are not become final. After going over the exceptions of aforesaid matter in German law, we are going to make a comparison with Turkish law. When comparing German and Turkish regulations with regards to the enforcement of unfinalised court decisions, it comes out that the regulations of Turkish law are more preferable in terms of practice. It is also going to explained that the provisional enforcement in German law is more different and more surprising as compared with Turkish law. It is going to concluded that Article 36 of Turkish Enforcement and Bankruptcy Code is a successful article in point of ensuring the benefit balance between creditor and debtor.
General Overview of German Law Regulations in Relation to Provisional Enforcement of Court Decisions (vorläufige Vollstreckbarkeit) and a Comparison with Turkish Law
Keywords: Hukuk